2014
DOI: 10.4103/1119-3077.144389
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, overweight, and underweight among urban Nigerians

Abstract: Obesity and overweight are common in our urban dwellers with accompanying regional differences. Attainment of middle age increases the likelihood of urban dwelling Nigerians to become overweight/obese. There is therefore the need to institute measures that will check development of overweight/obesity early enough, while improving the nutritional status of the few who may still be undernourished.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
39
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 2 publications
12
39
2
Order By: Relevance
“…[9] It was, however, lower than the 28.2% and 38.4% reported in two Nigerian studies. [16,25] The first study was community-based, the second HIV clinicbased, while ours was hospital-based: this might be the reason for the difference in the prevalence of overweight compared to that noted in our study.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…[9] It was, however, lower than the 28.2% and 38.4% reported in two Nigerian studies. [16,25] The first study was community-based, the second HIV clinicbased, while ours was hospital-based: this might be the reason for the difference in the prevalence of overweight compared to that noted in our study.…”
Section: Discussioncontrasting
confidence: 48%
“…[9,10,16,20] Unlike our study which was carried out in an outpatient clinic, these studies were community-based with much larger population sizes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Tanzania, prevalence of obesity and overweight was 40 % and 35 %, respectively and this was higher than 32.54 % and 23.44 % reported in 2012, respectively [25]. In Nigeria, the prevalence of overweight and obese in a study in 2011 was 22 % and 4 %, while in 2014 another reported prevalence of 31 % and 17 %, respectively [33] Okafor et al, 2014; these values are much lower than 37 % and 31 % found in our study.…”
Section: Discussionmentioning
confidence: 98%
“…That's indicated the physical fitness level and economic and social development is not coordinated in the similar level of economic development regions. Studies such as Fan et al (Fan et al 2012;Okafor et al 2014;) have shown that the higher the standard of living, the more likely to suffer from chronic diseases which caused by over nutrition and exercise too little. Jiang (Jiang et al 1998) have suggested to institute a regional evaluation standards, integrating the national physical fitness into the social development evaluation index that the purpose is arouse people's attention to exercise.…”
Section: Introductionmentioning
confidence: 99%